Solitary Neurofibroma of the Anterior Hard Palate: A Rare Presentation with Atypical Radiographic Features - Karthikeya Patil; Sanjay Chikkarasinakere Jogigowda; Varusha Sharon Christopher; Ritu Basavarajappa (Journal of the California Dental Association)
Introduction Neurofibroma is a benign peripheral nerve sheath tumor that commonly presents as part of neurofibromatosis syndrome. Solitary neurofibromas of the oral cavity are relatively rare, with various documented locations including the tongue, buccal mucosa, and palate. This case report presents a unique clinical manifestation of a solitary neurofibroma located in the anterior hard palate, a site that has not yet been documented in literature for non-syndromic neurofibromas.Materials and Methods We present a case of a patient with a solitary mass in the anterior region of the hard palate. A comprehensive clinical examination, radiographic evaluation, and histopathological analysis were performed. The patient’s medical history was thoroughly reviewed to rule out neurofibromatosis or other syndromes. The lesion was surgically excised and subjected to histopathological examination for definitive diagnosis.Results Histopathological examination confirmed the diagnosis of neurofibroma without any evidence of malignancy. No clinical features suggestive of neurofibromatosis type 1 or 2 were identified in the patient. The lesion presented as a well-defined, asymptomatic mass in the anterior hard palate. Post-operative healing was uneventful with no recurrence observed during the follow-up period.Conclusion To our knowledge, this is the first documented case of a solitary neurofibroma not associated with any syndrome in the anterior region of the hard palate. By highlighting this atypical presentation, our findings contribute valuable insights to the existing body of knowledge, potentially aiding clinicians in considering solitary neurofibromas as a differential diagnosis for palatal masses, even in the absence of systemic neurofibromatosis. This case report emphasizes the importance of histopathological examination in the definitive diagnosis of oral lesions and expands our understanding of the variability of neurofibroma presentations in the oral cavity.